A Facile and One‐Step Synthesis of Visible‐Light‐Responsive Silver and Mesoporous Carbon Comodified Carbon–Zinc Oxide Composites. Issue 9 (23rd June 2015) - Wang, Fangxiao; Liang, Lin; Shi, Lei; Liu, Mengshuai; Sun, Jianmin
Abstract Silver and mesoporous carbon (mC) comodified CZnO composites (Ag/mC/CZnO) were fabricated by a facile, one‐step process directly from C, Ag, and Zn precursors in CO2‐expanded ethanol, which provided a unique medium and did not require additional precipitant and mesoscaled organic templates. When the composite photocatalyst was applied to the degradation of rhodamine B and phenol, Ag/mC/CZnO exhibited excellent photocatalytic activity in visible light. The remarkably improved catalytic activity of the composites was attributed to the following synergistic effects. The modification of mC enriched the adsorption of pollutants on the photocatalyst. Additionally, the mesopores of carbon provided a spacious path for the separation of photogenerated electrons and holes. In addition to mC, carbon was also doped into ZnO, which narrowed the ZnO band gap. The modification of silver strengthened the absorbance of the visible region and improved the electron‐trapping ability.